2018
DOI: 10.1002/ange.201810460
|View full text |Cite
|
Sign up to set email alerts
|

Low Heat of Adsorption of Ethylene Achieved by Major Solid‐State Structural Rearrangement of a Discrete Copper(I) Complex

Abstract: The trinuclear copper(I) pyrazolate complex [Cu 3 ] rearranges to the dinuclear analogue [Cu 2 ·(C 2 H 4 ) 2 ]w hen exposed to ethylene gas.R emarkably,t he [Cu 3 ]$[Cu 2 ·-(C 2 H 4 ) 2 ]r earrangement occurs reversibly in the solid state. Furthermore,this transformation emulates solution chemistry. The bond-making and breaking processes associated with the rearrangement in the solid-state result in an observed heat of adsorption (À13 AE 1kJmol À1 per Cu-C 2 H 4 interaction) significantly lower than other Cu-C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…[26] Non-porous small molecule adsorbents are an emerging class of materials that can overcome the traditional trade-offs between selectivity vs capacity and selectivity vs heat of adsorption. [27][28] Though these materials can be limited by their relatively low surface areas, the adsorption of small alkenes such as ethene and propene can be rapid. Recently, we reported that trinuclear copper(I) complexes { [3,5- Figure 1) and {[4-Br-3,5-(CF 3 ) 2 Pz]Cu} 3 ([CuÀ Br] 3 ) bind small olefins like ethene reversibly, both in the solid-state and in solutions, and serve as remarkably effective, selective, and energy efficient ethene/ethane separation materials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[26] Non-porous small molecule adsorbents are an emerging class of materials that can overcome the traditional trade-offs between selectivity vs capacity and selectivity vs heat of adsorption. [27][28] Though these materials can be limited by their relatively low surface areas, the adsorption of small alkenes such as ethene and propene can be rapid. Recently, we reported that trinuclear copper(I) complexes { [3,5- Figure 1) and {[4-Br-3,5-(CF 3 ) 2 Pz]Cu} 3 ([CuÀ Br] 3 ) bind small olefins like ethene reversibly, both in the solid-state and in solutions, and serve as remarkably effective, selective, and energy efficient ethene/ethane separation materials.…”
Section: Introductionmentioning
confidence: 99%
“…Non‐porous small molecule adsorbents are an emerging class of materials that can overcome the traditional trade‐offs between selectivity vs capacity and selectivity vs heat of adsorption [27–28] . Though these materials can be limited by their relatively low surface areas, the adsorption of small alkenes such as ethene and propene can be rapid.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9][10][11][12][13][14][15][16][17] Beyond that, ordered materials constructed from CTCs are being pursued in very recent years for their controllable skeletons and excellent optical/catalytic performances. [18][19][20][21][22][23][24][25] The clusters herein are formed by sandwiching a foreign closed-shell metal cation between two gold(I) CTC molecules, resulting in an [Au 3 ]…M + …[Au 3 ] chemical formula for the resulting heptanuclear cluster. [6,[26][27][28][29][30][31][32] Since they were discovered in 1998, [28] few reports on structure determinations and luminescence properties only cover the central metal cations of Ag + and Tl + .…”
Section: Introductionmentioning
confidence: 99%